Honokiol attenuates lipotoxicity in hepatocytes via activating SIRT3-AMPK mediated lipophagy - Jingxin Liu; Tian Zhang; Jianzhong Zhu; Shuangchen Ruan; Rongsong Li; Bing Guo; Ligen Lin (BMC, 2021)
Abstract Background Non-alcoholic fatty liver disease (NAFLD) is characterized by ectopic accumulation of triglycerides in the liver. Emerging evidence has demonstrated that lipophagy regulates lipid mobilization and energy homeostasis in the liver. Sirtuin 3 (SIRT3), a mitochondrial NAD+-dependent deacetylase, modulates the activities of several substrates involving in autophagy and energy metabolism. Honokiol (HK) is a natural lignan from the plants of Magnolia genus that exhibits potent liver protective property. Methods AML12 was challenged with 500 μM palmitic acid and 250 μM oleic acid mixture solution to induce lipotoxicity. C57BL/6J mice were fed with a choline-deficient high fat diet (CDHFD) to generate liver steatosis. The expression of autophagy-related and AMP-activated protein kinase (AMPK) pathway proteins was evaluated by Western blotting and immunofluorescence staining. Intracellular lipid accumulation was validated by Nile red staining. Molecular docking analysis was performed on AutoDock 4.2. Results HK (5 and 10 μM) was found to attenuate lipid accumulation through promoting SIRT3-AMPK-mediated autophagy, mainly on lipid droplets. HK had hydrophobic interaction with amino acid residues (PHE294, GLU323 and VAL324) and NAD+. Moreover, HK improved mitochondrial function to enhance lipolysis, through decreasing the acetylated long-chain acyl-CoA dehydrogenase level. In CDHFD-fed mice, HK (2.5 and 10 mg/Kg) treatment obviously prevented lipid accumulation in the liver. And co-treatment of the AMPK inhibitor, Compound C, almost abolished the above changes. Conclusions These results suggest that HK could ameliorate lipotoxicity in hepatocytes by activating SIRT3-AMPK-lipophagy axis, which might be a potential therapeutic agent against NAFLD.